Analisis Perbandingan Sistem Pelaporan Kinerja Kementerian Dalam Negeri menggunakan Metode Usability Testing - Ardaneswari, Awanda; Manongga, Daniel H.F; Sembiring, Irwan (Universitas Hamzanwadi, 2025)
Performance Evaluation System for Apparatus Positions (Sikerja) is a web-based application owned by the Ministry of Home Affairs (MoHA), used to assess and measure the performance of civil servants across all units within MoHA. Currently, MoHA uses two versions of the Sikerja application: the old Sikerja and the new Sikerja. The purpose of this study is to compare the usability levels between 2 systems using the usability testing method, focusing on the performance input menu. The study employs a quantitative descriptive approach using a survey method involving 100 respondents from the Directorate General of Regional Governance, with a questionnaire as the research instrument. The questionnaire items are derived from the five usability indicators based on Jacob Nielsen's framework. The results of the validity and reliability tests on the questionnaire confirmed that it is valid and reliable. Subsequently, a descriptive analysis was conducted for each usability indicator. The analysis results show that the learnability score of the old Sikerja system is 3.24 (high), efficiency is 2.18 (moderate), memorability is 2.98 (moderate), errors is 1.88 (low), and satisfaction is 3,17 (high). On the other hand, the new Sikerja system has a learnability score of 2,23 (moderate), efficiency of 2.07 (moderate), memorability of 1.02 (low), errors of 2.77 (moderate), and satisfaction of 2.54 (moderate). It can be concluded that the new Sikerja system requires workflow simplification, increased user training and socialization, and regular evaluation for employees. These recommendations are expected to improve the usability score of the new Sikerja system within the Ministry of Home Affairs.